ANALISIS PEMAHAMAN MAHASISWA TERHADAP KONSEP DASAR ASET, KEWAJIBAN, EKUITAS, DAN JURNAL DALAM MENINGKATKAN EFEKTIVITAS PRAKTIK KERJA LAPANGAN - Ummarha, Nadhifah Yonas; Rissi, Dita Maretha; Sriyunianti, Fera; Ermatati Hatta (LP2M Politeknik Jambi, 2023)
This research aims to understand students' comprehension of the fundamental concepts of assets, liabilities, equity, and journals in enhancing the effectiveness of Work Practice (Internship). The study employs a qualitative research approach, with the research informants being 30 students from the Accounting Department of Politeknik Negeri Padang, selected based on their GPA grouping. The research was conducted on final-year students of the Accounting Department of Politeknik Negeri Padang for the academic year 2022/2023, namely the Diploma of Accounting and Applied Bachelor of Accounting. The research findings indicate that (1) a number of students with an accounting background have an initial advantage in comprehending basic accounting concepts. (2) several conditions related to students' understanding of the concepts of assets, liabilities, equity, and journals were identified. (3) enhancing students' comprehension and improving the effectiveness of fieldwork practices, collaborative efforts between educational institutions and relevant industry stakeholders are necessary